PEGylation of SPIONs by polycondensation reactions: A new strategy to improve colloidal stability in biological media - Viali, Wesley Renato [UNESP]; Da Silva Nunes, Eloiza [UNESP]; Dos Santos, Caio Carvalho [UNESP]; Da Silva, Sebastião William; Aragón, Fermin Herrera; Coaquira, José Antonio Huamaní; Morais, Paulo César; Jafelicci Júnior, Miguel [UNESP] (Springer Nature, 2013)
In this study, we report on a new route of PEGylation of superparamagnetic iron oxide nanoparticles (SPIONs) by polycondensation reaction with carboxylate groups. Structural and magnetic characterizations were performed by X-ray diffractometry (XRD), transmission electron microscopy (TEM), thermogravimetric analysis (TGA), and vibrating sample magnetometry (VSM). The XRD confirmed the spinel structure with a crystallite average diameter in the range of 3.5-4.1 nm in good agreement with the average diameter obtained by TEM (4.60-4.97 nm). The TGA data indicate the presence of PEG attached onto the SPIONs' surface. The SPIONs were superparamagnetic at room temperature with saturation magnetization (M S) from 36.7 to 54.1 emu/g. The colloidal stability of citrate- and PEG-coated SPIONs was evaluated by means of dynamic light scattering measurements as a function of pH, ionic strength, and nature of dispersion media (phosphate buffer and cell culture media). Our findings demonstrated that the PEG polymer chain length plays a key role in the coagulation behavior of the Mag-PEG suspensions. The excellent colloidal stability under the extreme conditions we evaluated, such as high ionic strength, pH near the isoelectric point, and cell culture media, revealed that suspensions comprising PEG-coated SPION, with PEG of molecular weight 600 and above, present steric stabilization attributed to the polymer chains attached onto the surface of SPIONs. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Colloidal stability; Iron oxide; Magnetic fluid; PEG; SPIONs; Surface modification; Colloidal Stability; Dynamic light scattering measurement; Magnetic characterization; Polycondensation reactions; Polymer chain length; Superparamagnetic iron oxide nanoparticles; Vibrating sample magnetometry; Carboxylation; Cell culture; Chain length; Ionic strength; Iron oxides; Magnetic fluids; Plastic coatings; Polyethylene glycols; Stabilization; Superparamagnetism; Surface treatment; Thermogravimetric analysis; Transmission electron microscopy; X ray diffraction analysis; Suspensions (fluids); citric acid; macrogol; polymer; superparamagnetic iron oxide nanoparticle; cell culture; colloidal stability; dispersion; ionic strength; isoelectric point; light scattering; magnetometry; measurement; molecular weight; pH; physical phenomena; polymerization; priority journal; room temperature; thermogravimetry; transmission electron microscopy; X ray diffraction